Microalgae harvesting techniques: updates and recent technological interventions. (3rd April 2023) - Kumar, Niwas; Banerjee, Chiranjib; Negi, Sangeeta; Shukla, Pratyoosh
Abstract: Microalgal biomass has garnered attention as a renewable and sustainable resource for producing biodiesel. The harvesting of microalgal biomass is a significant bottleneck being faced by the industries as it is the crucial cost driver in the downstream processing of biomass. Bioharvesting of microalgal biomass mediated by: microbial, animal, and plant-based polymeric flocculants has gained a higher probability of utility in accumulation due to: its higher dewatering potential, less toxicity, and ecofriendly properties. The present review summarizes the key challenges and the technological advancements associated with various such harvesting techniques. The economic and technical aspects of different microalgal harvesting techniques, particularly the cationic polymeric flocculant-based harvesting of microalgal biomass, are also discussed. Furthermore, interactions of flocculants with microalgal biomass and the effects of these interactions on metabolite and lipid extractions are discussed to offer a promising solution for suitability in selecting the most efficient and economical method of microalgal biomass harvesting for cost-effective biodiesel production.